Ajaran Agama Hindu dalam Kisah Atma Prasangsa - Ida Bagus Putu Eka Suadnyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Hinduism in conveying the teachings of his religion is not only always conveyed through dharma discourse, but also done through literary works, one of which is the story of Atma Prasangsa. This story tells the spiritual journey of Bhagawan Penyarikan. During his journey, the bhagawan saw how the atma was treated in such a way, there were those who were given gifts but also were repeatedly tortured. Therefore the author is interested in examining the story of this Atma Prasangsa to find out how the Atma Prasangsa story is, and what Hindu theological concepts are contained in the Atma Prasangsa story. This study uses a qualitative design, in conducting research on the story of Atma Prasangsa using research methods that are designed first determine the object of research, determine the source and type of data, determine research instruments, determine data collection techniques, conduct data analysis and test data validity. From the results of the study it was found that the contents of the story of Atma Prasangsa tell the story of the spiritual journey of Bhagawan in the extraction and recounting the karma pahala of Atma obtained at the time of the Atman world. In general, the story of Atma Prasangsa contains the concept of Hindu theology in the form of tattwa, susila and acara.